The Future of Feminist Liberalism - Nussbaum, Martha (2001)
Feminists have sometimes argued that philosophical theories of justice deriving from the liberal tradition cannot deal adequately with the concerns of women. I argue that in many ways this contention is mistaken: the best liberal theories of justice provide a very strong basis for thinking about what respect for human dignity requires. There are, however, two areas pertinent to sex equality in which even the strongest liberal theories have grave difficulty. First is the area of need and dependency. All theories of justice and morality deriving from the European social contract tradition fail to build into the basic social structure concern for care in times of asymmetrical dependency. The second problem I investigate is the problem of just distribution within the family. Focusing on the theory of John Rawls, I argue that his liberal commitment to seeing the family as a sphere of protected personal choice is in tension with his admission that the family is part of the "basic structure" of society. Moreover, the family does not exist by nature: it is always a construct of state action. The state should therefore make sure that this constructing is done well, compatibly with justice for women and children.